Real-World Assessment of Weight Change in People with HIV-1 After Initiating Integrase Strand Transfer Inhibitors or Protease Inhibitors - Yen-Wen Chen; Helene Hardy; Christopher D. Pericone; Wing Chow (Journal of Health Economics and Outcomes Research)
**Background:** Studies have shown an increase in weight among people living with human immunodeficiency virus (PLWH) who have also initiated integrase strand transfer inhibitors (INSTI). However, limited data are available regarding comparison of these changes with other antiretroviral regimens.